Pope's Chapel United Methodist Church Homecoming Service, October 1, 1972 - (:unkn) unknown (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Pope's Chapel United Methodist Church Homecoming Service, October 1, 1972. Event program. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19721001.pdf. 4 pages. 31433468 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Bohler, Clarence; Boyd, John; Buffington, W. L.; Bufford, Ethell; Butler, Dean; Chafin, Malcolm; Jones, Creighton; Jones, Lester; McIntosh, Brantley; Oglesby, Mack; Oglesby, Tommy; Phillips, Odell; Rucker, Prank; Sale, David; Satterfield, Walker; Smith, J. Leroy; Suttles, Albert; Wolfe, Ronny